An approach to model-following controller design based on a stabilized digital inverse system. (October 2015) - Tanaka, Ryo; Inoue, Shota; Shibasaki, Hiroki; Ogawa, Hiromitsu; Murakami, Takahiro; Ishida, Yoshihisa
This article explains our approach to designing a model-following controller based on a stabilized digital inverse system. We use an inter-sample auxiliary observation output from the model as an input to the inverse system. We then design the inverse system for minimum and non-minimum phase plants. In order to reposition the unstable poles of the inverse system on a stable region, we determine the optimal gain vector using a linear quadratic regulator. We confirm the effectiveness of our proposed method by performing simulations for several plants and conducting an experiment with a direct current motor.